Upaya UPAYA UIN SULTHAN THAHA SAIFUDDIN JAMBI DALAM MEMBERIKAN MOTIVASI DAN PENDAMPINGAN BAGI MAHASISWA DISABILITAS - Marda, Syahrul; Yuanita, Yuanita; Yunus, Abdullah; Salim, Agus (JIGC (Journal of Islamic Guidance and Counseling), 2024)
The government has made regulations for universities to be able to help students with disabilities in developing their potential, regulated in the Regulation of the Minister of Education and Culture of the Republic of Indonesia Number 46 of 2017 concerning Special Education, Special Service Education and Special Service Learning in Higher Education. UIN Sulthan Thaha Saifuddin Jambi through the Center for Disability Studies has an important role in efforts to provide motivation and assistance for students with disabilities to be able to foster enthusiasm in carrying out activities and lecture processes so that students with disabilities can have high intellect, master knowledge, and technology that develops continuously. This study uses a narrative approach so that researchers can focus on individual experiences with the Field Research method, namely data taken from the field using the Purposive Sampling technique. The efforts of UIN Sulthan Thaha Saifuddin Jambi in providing motivation and assistance can be classified into 3, namely students with disabilities who are deaf, deaf and visually impaired. The forms of policies, motivation and assistance in particular are the construction of facilities, infrastructure, fulfillment of assistive devices, installation of Braille symbols and sign language training. Meanwhile, in general, they are assistance for new students with disabilities, assistance in scholarship management, assistance with Real Work Lectures, Field Work Practice, motivation through workshop activities, Focus Group Discussion (FGD) and Counseling Guidance.